(untitled) (The Journal of Plant Protection Sciences, 2024)
During a random survey, one isolate of entomopathogenic nematode from ginger rhizosphere was collected from Faizabad district of Uttar Pradesh (India). Morphological and morphometric studies identified the isolate as Stein ernema carpocapsae. This was further confirmed by ITS-rDNA sequences analysis. Phylogenetic was constructed for studying relationship with known isolates. Pathogenic potential of the isolate of S. carpocapsae (IISR-EPN 06) on the larva of shoot borer (Conogethes punctiferalis), hairy caterpillar (Euproctis sp.) and greater wax moth (Galleria mellonella) was found under in vitro condition. Further this isolate displayed high virulence on above insect species. This study reported occurrence of a isolate of S. carpocapsae from ginger rhizosphere from India. This indigenous isolate could be investigated further for managing insect pests of ginger.